Techniques for Building Timing-Predictable Embedded Systems - Guan, Nan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book describes state-of-the-art techniques for designing real-time computer systems. The author shows how to estimate precisely the effect of cache architecture on the execution time of a program, how to dispatch workload on multicore processors to optimize resources, while meeting deadline constraints, and how to use closed-form mathematical approaches to characterize highly variable workloads and their interaction in a networked environment. Readers will learn how to deal with unpredictable timing behaviors of computer systems on different levels of system granularity and abstraction. Introduces promising techniques for dealing with challenges associated with deploying real-time systems on multicore platforms; Provides a complete picture of building timing-predictable computer systems, at the program level, component level and system level; Leverages different levels of abstraction to deal with the complexity of the analysis.
Introduction -- Part I Cache Analysis for WCET Estimation -- MRU Cache Analysis for WCET Estimation -- FIFO Cache Analysis for WCET Estimation -- Part II Real-Time Scheduling on Multicores -- Analyzing Preemptive Global Scheduling -- Analyzing Non-preemptive Global Scheduling -- Liu & Layland's Utilization Bound -- Parametric Utilization Bounds -- Cache-Aware Scheduling -- Part III Real-Time Calculus -- Finitary Real-Time Calculus -- EDF in Real-Time Calculus -- .
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation